Forbidden films censorship histories of 125 motion pictures - Sova, Dawn B. (Facts on File library of world literature, 2001)
Alphabetically arranged entries offer detailed histories of 125 films, providing production data, cast information, plot summaries, censorship histories, and profiles of directors.